2010
DOI: 10.1160/th10-02-0099
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory variation in heparin monitoring: Lessons from the Quality Management Program of Ontario coagulation surveys

Abstract: Unfractionated heparin (UFH) monitoring is subject to substantial interlaboratory variation. We analysed results of annual coagulation surveys administered by the Quality Management Program - Laboratory Services (Toronto, ON, Canada) from 2003 to 2007 to evaluate variation in UFH monitoring across Ontario. Participating laboratories performed an activated partial thromboplastin time (APTT) utilising their local methodology on lyophilised human plasma spiked with UFH. In the 2006 and 2007 surveys, laboratories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Studies evaluating inter-laboratory agreement in the context of heparin monitoring have failed to show that aPTT results correlate with anti-Xa results between different hospital laboratories. Moreover, greater variation was generally observed in the anti-Xa assay compared with the aPTT test [ 10 11 ]. Variations in anti-Xa measurements are observed when sample processing is delayed, as PF4 neutralizes heparin [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating inter-laboratory agreement in the context of heparin monitoring have failed to show that aPTT results correlate with anti-Xa results between different hospital laboratories. Moreover, greater variation was generally observed in the anti-Xa assay compared with the aPTT test [ 10 11 ]. Variations in anti-Xa measurements are observed when sample processing is delayed, as PF4 neutralizes heparin [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In response to the numerous limitations of the aPTT, researchers have evaluated direct heparin concentration monitoring using heparin anti-Xa levels. Compared to the aPTT, the heparin anti-Xa level is less impacted by biologic variables, but pre-analytic and analytic variability remain and can be considerable [ 19 ]. The anti-Xa is also more expensive than the aPTT, and is both less available and less familiar to clinicians.…”
Section: Guidancementioning
confidence: 99%
“…A French study has recently shown a 3 to 8 fold aPTT increase for an anti-Xa activity of 0.7 IU/mL (Table 1 ) [ 80 ]. Too sensitive reagents do not allow a precise chronometric measurement and therefore should not be used for UFH monitoring [ 81 , 82 ]. In addition, mechanical end point coagulometers showed greater sensitivity than optical ones [ 83 ].…”
Section: Biological Monitoring Of Anticoagulant Treatmentsmentioning
confidence: 99%
“…Similar reagent/instrument combinations showed less variation in aPTT results than unlike combinations [ 82 ]. Using the same instrument model and same reagent lot but performed in different laboratories, significant statistical and clinical differences in the heparin therapeutic range values are found, owing to variation in the individual plasma samples as well as pre-analytical and analytical variables that can vary greatly between hospitals.…”
Section: Biological Monitoring Of Anticoagulant Treatmentsmentioning
confidence: 99%